2016
DOI: 10.1007/s10811-016-0801-z
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic regulation of growth and fertility in the sporophyte of Dictyota dichotoma (Hudson) J.V. Lamouroux (Dictyotales, Phaeophyceae)

Abstract: While Dictyota dichotoma has been cultured for decades, relatively little is known on the abiotic regulation of its growth, life cycle and release periodicity. Here, we evaluated the different abiotic factors that potentially control growth, survival, fertility and spore release in order to establish efficient culture methods of the sporophyte that allow life cycle control. Vegetative growth is maximal at room temperature (18-20°C), but cultures can be stored for months at low temperatures (≈8°C). Red light, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 63 publications
(79 reference statements)
0
14
0
1
Order By: Relevance
“…In Saccharina japonica blue light promoted sporogenesis while red light inhibited sporangium formation (Mizuta et al 2007). Bogaert et al (2016) demonstrated that red light increased sporogenesis in Dictyota. Also the process of gamete release has been shown to be wavelength-specific.…”
Section: Light Quality and Identity Of Photoreceptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Saccharina japonica blue light promoted sporogenesis while red light inhibited sporangium formation (Mizuta et al 2007). Bogaert et al (2016) demonstrated that red light increased sporogenesis in Dictyota. Also the process of gamete release has been shown to be wavelength-specific.…”
Section: Light Quality and Identity Of Photoreceptorsmentioning
confidence: 99%
“…Critical levels of internal nitrogen and phosphorus are required to transform vegetative blades to sporangial sori in kelp species (Mizuta et al 1999, Kumura et al 2006. In Dictyota dichotoma, nutrient limitation has been shown to have a positive effect on sporogenesis (Bogaert et al 2016), reflecting the antagonism between growth and reproduction which is expected to be more pronounced in short-lived species. Similar results were presented for Dictyota kunthii by Hoffmann and Malbrán (1989).…”
Section: Nutrientsmentioning
confidence: 99%
“…Another hurdle is the inability to culture many brown algae for their full life cycle in vitro , thus limiting when questions might be asked (seasonally). Currently methods exist for Ectocarpus and Dictyota (Le Bail et al, 2011; Bogaert et al, 2016). In addition, it remains unclear how axenic growth conditions can become in this cultures while still supporting growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…If germlings were allowed to grow until a 7-9 cell stage, they 373 were able to survive 21 weeks of winter conditions. For D. dichotoma experiments have indeed 374 shown that sporophyte germlings from Roscoff can be conserved with limited growth at 375 temperatures as low as 8 °C (Bogaert et al 2016). These low temperatures also inhibit 376 sporogenesis.…”
Section: Potential Origin Of Introduced Populations 352mentioning
confidence: 99%
“…At present, populations of D. dichotoma are 107 subjected to large temperature gradients across this range. Temperature plays a prominent role 108 in the control of sporogenesis and growth in the species (Bogaert et al 2016), which could 109 influence its reproductive strategy. As the relative contribution of sexual and asexual 110 reproduction leaves a genetic signature within a species, we aim at integrating data from 111 phenological observations with population structure of D. dichotoma.…”
mentioning
confidence: 99%